Penerapan Metode Taguchi Untuk Meningkatkan Produktifitas pada Produksi LPG di PT.CVX - nana sugiono (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2018)
Abstract— One of the factors for maintaining existence of the product is keep the quality of products .The quality of products gas ( propane ) can be measured with the results of the percentage propane recovery and levels propane which passes to residue gas .Factor that influences quality control gas ( propane is the temperature at refrigerant system , speed refrigerant compressor , recycle valve opening of , the temperature at hot oil system , temperature tower , pressure tower and the flow of bait in every tower and one factor unrestrained the weather . Combination the level of factors on initial conditions used is a1b1c1d1e1f1g1 which are ( temperature refrigerant system at the temperature -27 & speed refrigerant compressor at 90 % speed, recycle valve opening of with temperature -27 & temperature hot oil system at the temperature 215 & temperature tower at the temperature 138 & pressure tower to pressure 200 psig and the flow of bait every tower in 1250 bbld with rerata propane recovery namely 90,56 % and levels propane which passes to residue gas namely 0,274 Taguchi method used to increase performance products .Based on a method of taguchi produced combination the level of a factor that is either by rerata the percentage propane recovery namely 91,04 % and rerata propane levels which passes to residue gas namely 0,263 % .Combination the level of factors that elected is a1b1c2d1e1f1g1 which are ( temperature refrigerant system at the temperature -27 f , speed refrigerant compressor at 90 % speed , recycle valve opening of with temperature -25 f , temperature hot oil system at the temperature 215 f , temperature tower at the temperature 138 f , pressure tower to pressure 200 psig and the flow of bait in every tower in 1250 bbld